Drought-induced transposon expression reveals complex drought response mechanisms in Brassica napus - Chen, Manyi; Luo, Dan; Kong, Hanzhao; Lv, Yan; Li, Chunsheng; Zhao, Yongguo; Huang, Qian; Lu, Guangyuan (Frontiers in Plant Science, 2025)
Transposable elements (TEs) are abundant components of plant genomes, yet their transcriptional activity and potential biological roles remain underexplored, especially under environmental stress conditions. This study investigates the transcriptional dynamics of TEs in Brassica napus during drought stress in seed development, aiming to uncover their contributions to stress responses and seed germination. RNA-seq data were analyzed for TE transcriptional activity in wild-type (WT) and BnaABI5 CRISPR-edited mutant lines of B. napus. A comprehensive computational pipeline was used to identify and characterize TE-derived transcripts, including protein-coding and long non-coding RNAs (lncRNAs). Functional annotation was performed for protein-coding TE transcripts located in intergenic regions to predict their involvement in biological processes. Out of 212,800 TEs identified in the B. napus genome, 17,547 were transcriptionally active, yielding 15,808 protein-coding transcripts and 1,739 lncRNAs. Among these, 65 protein-coding TE transcripts were identified as transposase genes, while 860 transcripts were predicted to represent novel genes derived from transposon regions, potentially participating in monocarboxylic acid metabolic processes. Specific to drought stress responses during seed germination, 128 protein-coding TE transcripts (including 5 transposases) and 37 lncRNAs were differentially expressed. Notably, the lncRNA transcripts MSTRG.108925.4 and MSTRG.109003.7 were implicated in regulating the PHD finger protein ALFIN-LIKE 1 (BnA10g0418090), contributing to drought tolerance mechanisms. This study highlights the functional relevance of TE transcription in the context of drought stress during seed germination, providing novel insights into TE-derived genes and lncRNAs as potential regulators of stress responses. These findings expand the understanding of TE biology in plants and offer valuable resources for future efforts to identify drought-resistant genes in B. napus.